The Index of Hero’s Power and Nobility in Shakespearean Tragedy Drama: A Semiotic Study - M. Yuseano Kardiansyah (Universitas Teknokrat Indonesia, 2016)
This paper discusses a study that investigates the index of hero’s power and nobility in Shakespearean tragedy dramas. Here, the discussion focuses on two works authored by William Shakespeare: